Patients With Coronary Endothelial Dysfunction Have Impaired Cholesterol Efflux Capacity and Reduced HDL Particle Concentration. Issue 1 (24th June 2016) - Monette, Jeffrey S.; Hutchins, Patrick M.; Ronsein, Graziella E.; Wimberger, Jake; Irwin, Angela D.; Tang, Chongren; Sara, Jaskanwal D.; Shao, Baohai; Vaisar, Tomas; Lerman, Amir; Heinecke, Jay W.
Abstract : Rationale: : Coronary endothelial dysfunction (ED)—an early marker of atherosclerosis—increases the risk of cardiovascular events. Objective: : We tested the hypothesis that cholesterol efflux capacity and high-density lipoprotein (HDL) particle concentration predict coronary ED better than HDL-cholesterol (HDL-C). Methods and Results: : We studied 80 subjects with nonobstructive (<30% stenosis) coronary artery disease. ED was defined as <50% change in coronary blood flow in response to intracoronary infusions of acetylcholine during diagnostic coronary angiography. Cholesterol efflux capacity and HDL particle concentration (HDL-PIMA ) were assessed with validated assays. Cholesterol efflux capacity and HDL-PIMA were both strong, inverse predictors of ED ( P <0.001 and 0.005, respectively). In contrast, HDL-C and other traditional lipid risk factors did not differ significantly between control and ED subjects. Large HDL particles were markedly decreased in ED subjects (33%; P =0.005). After correction for HDL-C, both efflux capacity and HDL-PIMA remained significant predictors of ED status. HDL-PIMA explained cholesterol efflux capacity more effectively than HDL-C ( r =0.54 and 0.36, respectively). The efflux capacities of isolated HDL and serum HDL correlated strongly ( r =0.49). Conclusions: : Cholesterol efflux capacity and HDL-PIMA are reduced in subjects with coronary ED, independently of HDL-C. Alterations in HDL-PIMA and HDL itself account for a much larger fraction of the variation in cholesterol efflux capacity than does HDL-C. A selective decrease in large HDL particles may contribute to impaired cholesterol efflux capacity in ED subjects. These observations support a role for HDL size, concentration, and function as markers—and perhaps mediators—of coronary atherosclerosis in humans.